Genetic diversity of lactase persistence in East African populations. (December 2016) - Hassan, Hisham; Erp, Anke; Jaeger, Martin; Tahir, Hanan; Oosting, Marije; Joosten, Leo; Netea, Mihai
Abstract Background The expression of lactase which digests lactose from milk in humans is generally lost after weaning, but selected mutations influencing the promoter of the lactase gene have spread into the human populations. This is considered a classical example of gene-culture co-evolution, and several studies suggested that the lactase gene has been under strong directional evolutionary selective pressure in the past 5000 to 10, 000 years. Results In the present study we investigated the distribution of three gene variants leading to lactase persistence in 12 different East African populations as well as one European population. Our results show that with the exception of Copts and Nilotic populations who are fully lactose non-persistent, the majority of populations of East Africa show at least partly lactose persistence, with both ethnic and socio-economic aspects playing an important role in the distribution of genetic variants. In this study, the variants C/G-13907 and T/G-13915, which are the major variants among the nomadic Arabs in the Arabia and Beja of East Africa, showed remarkable frequencies in Sudanese populations, especially those of pastoralists, in line with the historical links and bidirectional migration of nomadic populations between Arabia and East Africa. The C/T-13910 variant, generally associated with European populations is uniquely present among the Fulani. Conclusions These data indicate that a combination of socio-economic, ethnic and evolutionary factors converged to shape the genetic structure of lactase persistence in East African populations.